Neuropsychological and cognitive psychophysiological substrates of impulsive aggression - Barratt, Ernest S.; Stanford, Matthew S.; Kent, Thomas A.; Alan, Felthous (Biological psychiatry (1969), 1997)
The purpose of this study was to test whether subjects who commit impulsive vs non-impulsive aggression differ on measurements of personality, neuropsychology, and cognitive psychophysiology, and whether these differences can yield information regarding the etiology of impulsive aggression. Subjects were two groups of prison inmates, distinguished by their committal of impulsive or nonimpulsive aggression, and matched noninmate controls. All inmates met DSM III-R criteria for an antisocial personality disorder but for no other disorder. Impulsiveness, anger, and peak P300 latencies did not differ between the inmate groups, but verbal symbol decoding and peak P300 amplitudes did. Impulsiveness and verbal skills were inversely correlated. Impulsiveness was inversely correlated with, and verbal skills positively correlated with P300 amplitudes. The results indicate that aggression is not homogenous, even among antisocial persons, and that impulsive aggression is related to neuropsychological and cognitive psychophysiological measures of information processing beyond those factors related to criminality alone.